The Effect of Problem-Based Learning Model with Google Meet on Independence and Learning Outcomes - Firka Christin Hutasoit; Muhammad Yusuf Harahap; Eko Wahyu Nugrahadi (EDUTEC : Journal of Education And Technology, 2021)
This research aims to find out the Influence of Problem-Based Learning Models with Google Meet Media on Independence and Learning Outcomes of Students of Grade X State High School 1 Lubuk Pakam. Where the background is based on data from the Ministry of Education and Culture student learning outcomes seen from the achievement of the average National Examination (UN) score from 2015 to 2019 in economic subjects are very low plus due to emergency situations in the covid-19 pandemic, giving rise to the indonesian government's policy of learning from home through online learning patterns. In the current situation when learners learn at home following online learning provided by the teacher's mother while parents are not always present to accompany and monitor the process of student learning activities, then learning independence is needed so that students can follow learning activities and be responsible in completing the learning tasks of each subject. The goals to be achieved in this study include: (1) To know the difference in student learning outcomes taught using a problem-based learning model with google meet media is higher than student learning outcomes taught with a direct learning model, (2) To know the difference in learning outcomes of students who have high independence higher than learning outcomes that have low independence, (3) To know the interaction between problem-based learning models with google meet media and learning independence in influencing student learning outcomes. This research will be conducted in class X of State High School 1 Lubuk Pakam using a treatment by level 2 x2 research design using a two-track anava, a two-track anava with Quantitative Descriptive analysis techniques where a sample of 60 students and using experimental methods.